Feasibility of establishing an infant hearing screening program and measuring hearing loss among infants at a regional referral hospital in south western Uganda - Seguya, Amina; Bajunirwe, Francis; Kakande, Elijah; Nakku, Doreen (PLoS ONE, 2021)
Introduction Despite the high burden of hearing loss (HL) globaly, most countries in resource limited settings lack infant hearing screening programs(IHS) for early HL detection. We examined the feasibility of establishing an IHS program in this setting, and in this pilot program measured the prevalence of infant hearing loss (IHL) and described the characteristics of the infants with HL. Methods We assessed feasibility of establishing an IHS program at a regional referral hospital in south-western Uganda. We recruited infants aged 1 day to 3 months and performed a three-staged screening. At stage 1, we used Transient Evoked Oto-acoustic Emissions (TEOAEs), at stage 2 we repeated TEOAEs for infants who failed TEOAEs at stage 1 and at stage 3, we conducted Automated brainstem responses(ABRs) for those who failed stage 2. IHL was present if they failed an ABR at 35dBHL. Results We screened 401 infants, mean age was 7.2 days (SD = 7.1). 74.6% (299 of 401) passed stage 1, the rest (25.4% or 102 of 401) were referred for stage 2. Of those referred (n = 102), only 34.3% (35 of 102) returned for stage 2 screening. About 14.3% (5/35) failed the repeat TEOAEs in at least one ear. At stage 3, 80% (4 of 5) failed the ABR screening in at least one ear, while 25% (n = 1) failed the test bilaterally. Among the 334 infants that completed the staged screening, the prevalence of IHL was 4/334 or 12 per 1000. Risk factors to IHL were Newborn Special Care Unit (NSCU) admission, gentamycin or oxygen therapy and prematurity. Conclusions IHS program establishment in a resource limited setting is feasible. Preliminary data indicate a high prevalence of IHL. Targeted screening of infants at high risk may be a more realistic and sustainable initial step towards establishing IHS program s in a developing country like Uganda.
Keywords: Infant hearing; Screening program; south western; Uganda